2015
DOI: 10.1007/s00338-015-1333-8
|View full text |Cite
|
Sign up to set email alerts
|

Ghosts of thermal past: reef fish exposed to historic high temperatures have heightened stress response to further stressors

Abstract: International audienceIndividual exposure to stressors can induce changes in physiological stress responses through modulation of the hypothalamic–pituitary–interrenal (HPI) axis. Despite theoretical predictions, little is known about how individuals will respond to unpredictable short-lived stressors, such as thermal events. We examine the primary neuroendocrine response of coral reef fish populations from the Îles Eparses rarely exposed to anthropogenic stress, but that experienced different thermal historie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The thermal experience of fish, especially during early life, can shape HPI responsiveness on further stressors (Mateus et al ., 2017a; Mills et al ., 2015). Research effort is needed to understand how exposure to elevated temperatures during early life may affect the capacity to cope with the various threats caused by global warming (Mateus et al ., 2017a; Wassink et al ., 2019; Whitney et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The thermal experience of fish, especially during early life, can shape HPI responsiveness on further stressors (Mateus et al ., 2017a; Mills et al ., 2015). Research effort is needed to understand how exposure to elevated temperatures during early life may affect the capacity to cope with the various threats caused by global warming (Mateus et al ., 2017a; Wassink et al ., 2019; Whitney et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of viable pre-hatching eggs translates into reduced juvenile recruitment 29 . Furthermore, an early exposure to maternal GC levels during embryonic development causes permanent modification of the offspring’s HPA/I axis, and may impact future responses to environmental stressors, which may or may not be adaptive, and also may cause trade-offs between life-history traits later in life 48 , 49 . The duration of the environmental perturbation will also play an important role on the extent of the demographic consequences of physiological stress.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, prior work in warmer water has shown recovery to be complete by 4 h; for instance, a study of largemouth bass exercised at 10°C showed complete recovery of plasma cortisol and glucose levels by 2 h ) and work on northern pike has shown recovery of muscle lactate levels by 1 h (Arlinghaus et al 2009). The course of recovery of plasma metrics may be directly dictated by temperature, possibly due to reduced enzymatic activity in cold conditions (Van Ham et al 2003;Mills et al 2015). For instance, a study of Atlantic salmon Salmo salar L., Wilkie et al (1997) found recovery of plasma lactate levels by 4 h at relatively warmer temperatures (18°and 23°C), but not at lower temperatures (12°C).…”
Section: Discussionmentioning
confidence: 99%